Business Economics / Strategy and Applications - Cook Mark; Farquharson Corri (Pitman Publishing, 1998)
An economic textbook which explores the increasingly recognized links between business economics and strategy. Preface, Acknowledgements, Introduction, The Scope of Business Economics, The Organization and Its Environment, Business Objectives and Ethics and Corporate Governance, Alternative Models of the Organization, Demand and Revenue and Costs, Consumer Behavior, Demand and Elasticity, Estimating and Forecasting Demand, Determinants and Behavior of Costs, Marketing and Investment Decisions, Pricing Decisions, Pricing Practices, Non-Price Competition and the Marketing Mix, Investment Decisions and the Cost of Capital, Techniques for Decision Making under Conditions of Uncertainty and Risk, Economics and Corporate Strategy, Elements of Business Strategy, Analyzing the Structure of Competition, Competitive Weapons: Scale and Scope and Core Competences, Transaction Cost Economics, Deterrence and Reputation as Strategic Tools, Quality and the Economics of the Organization, Business Issues, Business Issues and the Environment, The Globalization of Business Activities, Index.